Pengaruh Model Traffic pada Kinerja Protokol Routing DSDV dalam MANET - Asika Ayu Wandira; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
MANET (Mobile Ad-Hoc Network) is a network where each of its nodes can adapt to Mobile conditions. The protocols contained in MANET are divided into three types: proactive, reactive and hybrid. The Destination Sequence Distance Vector (DSDV) is one of the proactive protocol types. In MANET (Mobile Ad-Hoc Network) There are frequent routing problems such as looping. To handle this, use the DSDV protocol where this protocol uses a sequence number to avoid the occurrence of looping on the MANET network. Traffic models used are traffic CBR and Exponential. The simulation program is done using Network Simulator 3.21 (NS-3.21) in the Ad-Hoc Network (MANET) Mobile network. The test parameters are used in the form of Packet delivery ratio (PDR),throughput, and average end-to-end delay. Based on the simulation that has been done shows that the DSDV protocol has a good performance by using exponential traffic judging by the PDR test value and its end-to-end delay. Judging from the value of traffic throughput CBR has a higher value compared to Exponential traffic. Traffic CBR with an average value of PDR 55.31%,throughput 319.9 and an average end-to-end delay of 1.377 seconds. Compared to the results exponential traffic is with the average value PDR 63.74%, throughput 312.8 and average end-to-end delay 1.289 s.